WHY IS IT IMPORTANT FOR CORPORATIONS TO PLAY A ROLE IN SUSTAINABILITY? (Utah Environmental Law Review; Vol 31 No 1 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} I was asked to participate in a panel to discuss the role that corporations play in helping to create a sustainable society. Since my natural tendency is to look to those factors I can influence before commenting on what other individuals and groups "should" be doing, I will focus most of my remarks on the role of higher education in sustainability. David Solnit, Naomi Klein, David Korten and others suggest that the corporate structure itself is responsible for many of the environmental and social problems we are facing. On issues ranging from the unintended consequences of industrial production and globalization, environmental and safety violations, greenwashing of marketing campaigns, the driving force of unchecked consumerism, and climate change, they make a compelling case that corporations have had an enormous negative impact on our environment.